STUDI EMPIRIS MENGENAI PENERAPAN METODE SAMPLING AUDIT DAN FAKTORFAKTOR YANG MEMPENGARUHI PENGGUNAAN METODE SAMPLING AUDIT OLEH AUDITOR BPK - Surya Raharja (Jurnal Bisnis dan Ekonomi, 2008)
To obtain the adequate evidence, auditor does not have to test all existing transaction.Along of cost benefit consideration, it is impossible for auditor to test all transaction evidence.Based on this consideration; then in profession recognized widely that most evidence obtainedusing sampling. The limited audit sampling research motivated the writer to conduct this research.This research is a development from previous researches by Hall of et al. (2002) and Zarkasyi(1992). Researcher take the governmental auditor (BPK) as research subjects because samplingproblems in goverment audit differ from the practice make an audit of the private sector (Arkin,1982). The purpose of this research is portraying how sampling audit practice in BPK and explorefactors affecting the use of sampling method by governmental auditors...The responses from 122 respondents show 70,5% respondents did not use the statisticalsampling method. In nonstatistics sample selection method, two techniques which less get thesupport empirically namely haphazard and block sampling, in the second (32,6%) and third rank(11,6%). There is indication of selection bias mostly in size, measure, and location. Mostrespondents (76,25%) answered that they did not get formal training in avoiding selection bias.But that way only 36,9% respondents replied they did not use the procedures to mitigate theselection bias.There are four factors which hypothesized affecting the method used in audit sampling.These factors are auditor perception to statistical sampling method, auditor perception toperceived audit risk, time pressure and experience. Result from logit regression test indicated thatamong four factors hypothesized, only perception factor to statistical sampling method issignificantly influent to the method used in audit sampling.Key words: Sampling Audit, Governmental Auditor, Selection Bias.